Technology MATLAB in problems of compression nesferychnyh cavity in a fluid - Буйвол, В. М.; Фоміна, Н. Б.; Наконечна, В. В. (Problems of Informatization and Control, 2009)
Results of calculations and analysis features of flows near elipsoyidalnyh cavity. Calculations are made based on a mathematical hydrodynamic model of closed-free surfaces in fluids, which one of the authors developed earlier, as well as technology Matlab